Aspectos ultra estruturais de cócleas de cobaias expostas a agrotóxico e ginkgo biloba - Finckler, Andréa Dulor (2010)
Brazil is among the world's largest consumers of pesticides and their increased use is given in agriculture, especially monoculture in large areas. Research shows that the ototoxic agents, in addition to compromising the peripheral auditory and vestybular systems, they may cause changes in central auditory pathways. O objetivo deste estudo foi verificar os aspectos ultra-estruturais de cócleas de cobaias expostas a agrotóxico e ginkgo biloba, utilizando doses comprovadamente ototóxicas, lesivas às células ciliadas externas, avaliando-se as alterações anatômicas através da microscopia eletrônica de superfície. The aim of this study was to evaluate the ultrastructural aspects of the cochlea of guinea pigs exposed to pesticides and ginkgo biloba, using ototoxic doses, damaging the outer hair cells, to evaluate the anatomic changes by surface electron microscopy. This is a prospective experimental study, conducted in guinea pigs, wich the inclusion criterion was the presence of DPOAE. The sample was divided into five groups, in which they administered 0.9% saline solution (group 1 - control), pesticides - 0.3 mg / kg / day (group 2), Ginkgo biloba - 100mg/kg/day, 90 minutes after a pesticide 0.3 mg / kg / day (group 3), pesticides - 3 mg / kg / day (group 4) and Ginkgo biloba - 100mg/kg/day, 90 minutes after a pesticide 3.0 mg / kg / days (group 5) for seven consecutive days. The pesticide used was that of methamidophos from Fersol ®. The anatomical evaluation was performed with scanning electronic microscopy. The guinea pigs subjected to pesticides showed morphological cochlear lesions in the three turns analyzed by electronic microscopy, intensified according to the dosage received from the pesticide agent. Guinea pigs treated with pesticides and Ginkgo biloba showed a maintenance of ciliary architecture in outer hair cells in all cochlear turns, whereas in the group treated only with pesticides, there was disappearance of the cilia of outer hair cells and distortion in the architecture of cilia remaining the MoU. We conclude that the greater the exposure to pesticides increased the damage in outer hair cells of the cochlea of albino guinea pigs, while those who had previously received ginkgo biloba keep outer hair cells cytoarchitecture preserved.